Correlation between Clinical Findings and Per-Operative Findings ofStomach Cancer (The Planet, 2024)
Introduction: Gastric cancer remains a leading cause of cancer-related mortality globally, with significant diagnostic and treatment challenges. This study aimed to investigate the correlation between clinical findings and per-operative findings in patients diagnosed with stomach cancer, providing insights to enhance diagnostic accuracy and treatment planning. Methods & Materials: This cross-sectional study at Sylhet MAG Osmani Medical College Hospital from September 2022 to August 2023 included 100 stomach cancer patients undergoing surgery. Pre-operative evaluations and detailed per-operative findings were analyzed, with statistical methods used to identify predictors of tumor behavior. Results: The mean age of the patients was 55 years, with a male predominance (60%). Clinical symptoms included weight loss (70%), abdominal pain (50%), nausea (30%), and vomiting (20%). Physical examination revealed a palpable mass in 45% and ascites in 10% of patients. Laboratory results showed a mean hemoglobin level of 11.5 g/dL, with mean AST and ALT levels of 45 U/L and 50 U/L, respectively. Imaging findings indicated an average tumor size of 4.2 cm, with 40% showing lymph node involvement. Per-operative findings revealed localized tumors in 30%, regional spread in 50%, and distant metastasis in 20% of patients. Conclusion: This study highlights the importance of integrating clinical, laboratory, and imaging findings to improve the accuracy of gastric cancer staging and treatment planning. The identified predictors of per-operative findings can guide clinicians in tailoring individualized treatment strategies, ultimately enhancing patient outcomes.
Keywords: Gastric cancer; Clinical findings; Per-operative findings; Diagnostic evaluation; Predictive analysis